Recognizing Psychosis in Autism Spectrum Disorder - Ribolsi, Michele; Fiori Nastro, Federico; Pelle, Martina; Medici, Caterina; Sacchetto, Silvia; Lisi, Giulia; Riccioni, Assia; Siracusano, Martina; Mazzone, Luigi; Di Lorenzo, Giorgio (Frontiers in Psychiatry, 2022)
There is strong evidence for the existence of a high comorbidity between autism and psychosis with percentages reaching up to 34.8 % and several signiﬁcant implications for treatment and prognosis of these patients. However, the identification of comorbid psychosis in patients with Autism Spectrum Disorder represents a complex challenge from a psychopathological point of view, in particular in patients with greater deficits in verbal communication. Intercepting the onset of a psychotic breakdown in autism may be very difficult, both disorders in fact occur along a phenotypic continuum of clinical severity and in many cases, psychotic symptoms are present in an attenuated form. In this paper we reviewed the available scientific literature about comorbidity between psychosis and autism, focusing our attention on four specific dimensions: delusions, hallucinations, negative symptoms and clinical course. The aim of this paper is to provide clinical tools to identify these psychotic phenomena in autistic patients, even when they occur in their attenuated form.